2019
DOI: 10.1177/2325958219867315
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Cerebral Toxoplasmosis Revisited: Current Concepts and Controversies of an Old Disease

Abstract: Cerebral toxoplasmosis is the most common cause of expansive brain lesions in people living with HIV/AIDS (PLWHA) and continues to cause high morbidity and mortality. The most frequent characteristics are focal subacute neurological deficits and ring-enhancing brain lesions in the basal ganglia, but the spectrum of clinical and neuroradiological manifestations is broad. Early initiation of antitoxoplasma therapy is an important feature of the diagnostic approach of expansive brain lesions in PLWHA. Pyrimethami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
163
1
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(189 citation statements)
references
References 196 publications
(370 reference statements)
2
163
1
23
Order By: Relevance
“…2,7,8 Cerebral toxoplasmosis is fatal if untreated and a major cause of death in HIV-infected patients from low-and middle-income countries. [7][8][9] Cellular response is totally altered in HIV-infected patients. Th1/ Th2 imbalance due to HIV and the decrease in CD4 T cells (CD4 T-lymphocyte counts below 100 cells/µL) lead to reactivation of latent toxoplasmosis due to a fail of antiparasitic CD4 T-cell response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7,8 Cerebral toxoplasmosis is fatal if untreated and a major cause of death in HIV-infected patients from low-and middle-income countries. [7][8][9] Cellular response is totally altered in HIV-infected patients. Th1/ Th2 imbalance due to HIV and the decrease in CD4 T cells (CD4 T-lymphocyte counts below 100 cells/µL) lead to reactivation of latent toxoplasmosis due to a fail of antiparasitic CD4 T-cell response.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more effective strategies are required for differential diagnosis. 7,8 For this propose, studies have been shown that microRNAs (miRNA, miR) play an important role in regulating gene expression in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…The infection by Toxoplasma gondii is frequent around the world and its prevalence range from <30% to more than 60% (Pappas et al, 2009;Dubey et al, 2012;Wallon and Peyron, 2018;Greigert et al, 2019). Different clinical forms of toxoplasmosis resulting from the infection by this Apicomplexan parasite arises and drawn attention especially for pregnant women, newborns and other immunosuppressed patients (Robert-Gangneux and Dardé, 2012;Neu et al, 2015;Rostami et al, 2019;Vidal, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 HIV+ patients may also present brain damage caused by opportunistic diseases developed due to their immune-compromised status, such as cerebral toxoplasmosis (CT). [6][7][8] CT is a possible complication of Toxoplasma gondii infection, a common protozoa spread worldwide. About a third of the world's population is possibly infected with T. gondii, 8 with 80% of those as asymptomatic carriers.…”
Section: Introductionmentioning
confidence: 99%
“…7 Given the variety of possible symptoms, diagnosis of CT requires confirmation through histological and laboratorial means. 7 CT patients may show long-lasting cognitive impairment due to brain abscesses, including deficits to the executive functions, lower processing speed and language. 7,9 Another contributing factor to neurocognitive impairment on HIV+ patients worldwide is alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%